Experimental regulating parameters of bladder-type hydraulic accumulator - Zhuk, Volodymyr; Verbovskyi, Orest; Ihor, Popadiuk (Zielona Góra: Uniwersytet Zielonogórski)
Experimental regulating parameters of the non-stationary expansion of air inside a bladder-type hydraulic accumulator, working with the simple short pipeline, are presented in the paper. The technique of continuous online monitoring of changes in time of volume and absolute air pressure inside the hydraulic accumulator during the discharge process has been improved. Three series of experimental studies of transient gas processes inside the accumulator at different values of the average volume flow rate are made.
Keywords: discharge cycle; hydraulic accumulator; non-stationary expansion; polytropic index; storage volume